Butterfly technique: what happens when swimmers get tired? - Osborough, C.; Peyrebrune, M. (coachesinfo.com)
Despite several studies that have considered race performance, none have described the potential changes in technique that occur during the stressful conditions of maximal repeat sprinting often used in training. The aims of this article are to assess the effect of repeated sprinting and muscular fatigue on butterfly swimming technique, and to discuss the applications and implications of this research to coaching and training.